THE EFFECTS OF A SIX-MONTH TRAINING PROGRAMME ON RUNNING ENDURANCE, MORPHOLOGICAL CHARACHERISTICS AND SOME AEROBIC ABILITY PARAMETERS OF ADULT WOMEN WITH DIFFERENT PHYSICAL ABILITIES - Matej Plevnik; Rado Pišot; Branko Škof (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2012)
This study reveals the results of a six-month training programme between a recreational group of previously physically inactive women (Group 1) and an already regularly active recreational group of female runners (Group 2). The sample consisted of 28 women, 13 in Group 1 (age (yr) = 41.7 ± 14.3, BMI = 26.8 ± 3.4) and 15 in Group 2 (age (yr) = 38.3 ± 7.8, BMI = 21.5 ± 1.7). Despite different initial values, the results in both groups showed an improvement in measured parameters that were more pronounced in Group 1; however, in comparisons carried out between the two groups, only Group 1 achieved a statistically significant improvement in relative maximal oxygen uptake (ml/min/kg). The results demonstrate that the recommendations of the World Health Organization (WHO), whose guidelines suggests at least 30 min of physical activity per day, are suitable for improving and maintaining functional abilities, including those of previously inactive groups (Group 1) as well as recreational groups (Group 2) of female runners.